Comparison of the Genetic Organization, Expression Strategies and Oncogenic Potential of HTLV-1 and HTLV-2. (29th December 2011) - Rende, Francesca; Cavallari, Ilaria; Romanelli, Maria Grazia; Diani, Erica; Bertazzoni, Umberto; Ciminale, Vincenzo
Abstract : Human T cell leukemia virus types 1 and 2 (HTLV-1 and HTLV-2) are genetically related complex retroviruses that are capable of immortalizing human T-cells in vitro and establish life-long persistent infections in vivo . In spite of these apparent similarities, HTLV-1 and HTLV-2 exhibit a significantly different pathogenic potential. HTLV-1 is recognized as the causative agent of adult T-cell leukemia/lymphoma (ATLL) and tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM). In contrast, HTLV-2 has not been causally linked to human malignancy, although it may increase the risk of developing inflammatory neuropathies and infectious diseases. The present paper is focused on the studies aimed at defining the viral genetic determinants of the pathobiology of HTLV-1 and HTLV-2 through a comparison of the expression strategies and functional properties of the different gene products of the two viruses.